Efficacy of Burst Mode Torsional Phacoemulsification in Age-Related Cataract (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Torsional ultrasound energy and burst mode interrupted energy delivery system are recent advancementsin the technique of phacoemulsification surgery. It has been reported that both these advancementshelpto reduce corneal wound burn and thermal induced endothelial cell loss and thereby helps to achieve excellent early postoperative visual outcomeObjectives: To evaluate the efficacy of burst mode torsional phacoemulsification surgery in age-related cataract.Materials and Methods: Prospective observational study of 120 cases that underwent phacoemulsificationcataract surgery in which torsional energy was used in burst mode. Phacoemulsification was performed by “vertical –chop” technique. Intraoperatively corneal wound burn, Descemet’s membrane detachment, posterior capsule ruptureetc.were evaluated. Postoperatively corneal oedema, best corrected visual acuity, cystoid macular oedema were evaluated. Postoperatively eyes were examined at day 1, 1 week, 6 weeks and 3 months.Results: Mean age of the patients was 57.28± 8.20 years. Most of the patients 81(67.5%) had nuclear sclerosis grade-II cataract.Intraoperatively, moderate wound burn occurred in 02(1.6%) eyes, localized Descemet’s membrane detachmentin 03(2.5%) eyes and posterior capsule rupture occurred in 03(2.5%) cases. Postoperatively, moderate and severe corneal edema was found in 06(5.0%) and 04(3.3%) eyes respectively at day 1. At the end of 3 months follow-up, 114(95%) eyes maintained a best corrected visual acuity of ≥ 6/18, of which 109(90.8%) eyes achieved ≥ 6/9.Conclusion: Burst mode torsional phacoemulsfication is a very effective and advanced technique of cataract surgery. Intraoperative complications are very less and visual outcome is excellent.Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 94-97